SCENARIO MODELING OF THE IMPACT OF INNOVATIVE AND TECHNOLOGICAL MODERNIZATION OF PRODUCTION ON THE EXPORT COMPETITIVENESS OF GRAIN ENTERPRISES OF UKRAINE - Shcherbak, Denys (Public Management and Policy, 2026)
This paper develops scenario-based modelling to quantify how innovation-driven technological modernization of grain production translates into export competitiveness of Ukrainian enterprises. The study operationalizes modernization effects through a net-back model of net export revenue. Five modernization scenarios are specified and calibrated to the 2025/26 marketing year export forecast (Q = 40.6 Mt; benchmark price P = 183 USD/t; baseline LogCost = 50 USD/t; prem = 0.02; disc = 0.03; risk = 0.0075). The scenarios differ in targeted competitive advantage channels: S1 (inertial) maintains basic practices; S2 (technological leadership) reduces unit costs and enhances quality control; S3 (cluster/cooperative) consolidates batches and lowers logistics/transaction costs; S4 (adaptive resilience) minimizes supply disruptions and risk premiums; S5 (premium-standard) focuses on EU compliance, traceability, and certification to capture price premiums. Simulation results demonstrate that modernization packages monetize production-level technological effects into a 13.4–19.0% increase in net export revenue relative to the inertial trajectory – from 5.27 bn USD (S1) to 5.98–6.27 bn USD under active modernization (2026 projection). Sensitivity analysis confirms the dominant role of logistics: a 10 USD/t reduction in LogCost adds +0.406 bn USD; a 1 percentage point improvement in net price correction (premium–discount) adds ≈0.074 bn USD; a 0.5 pp reduction in risk losses adds ≈0.037 bn USD. These effects remain robust under moderate parameter variations. The findings establish an evidence-based policy hierarchy: priority must be given to reducing export‑chain costs and war‑related risks, while quality, traceability and compliance instruments are essential for accessing premium segments and ensuring long‑term export resilience. Further research should focus on micro-level project valuation (NPV, IRR) for typical farm profiles and regionally differentiated risk parameters.